The Application of Accelerometer-Derived Moving Averages to Quantify Peak Demands in Basketball: A Comparison of Sample Duration, Playing Role, and Session Type. (14th December 2021) - Fox, Jordan L.; Conte, Daniele; Stanton, Robert; McLean, Blake; Scanlan, Aaron T.
Abstract: Fox, JL, Conte, D, Stanton, R, McLean, B, and Scanlan, AT. The application of accelerometer-derived moving averages to quantify peak demands in basketball: A comparison of sample duration, playing role, and session type. J Strength Cond Res 35(12S): S58–S63, 2021—The purpose of this was to study compare peak external workload intensities in basketball using accelerometer-derived moving averages between different sample durations (0.5–5 minutes), session types (training vs. game-play), and playing roles (starting vs. bench players). Five starting and 3 bench players were monitored over a 15-week competitive season using accelerometers. For all training sessions and games, peak external workload intensities were determined using accelerometer-derived moving averages for PlayerLoad per minute (PL·min −1 ) across sample durations of 0.5, 1, 2, 3, 4, and 5 minutes. Linear mixed-models and effect sizes (ESs) were used to compare peak PL·min −1 between sample durations, session type, and playing role. Peak PL·min −1 was significantly different between all sample durations ( p < 0.05; ES = 0.88–5.45), with higher intensities evident across shorter sample durations. In starting players, peak intensities were significantly higher during games compared with training for all sample durations ( p < 0.05; ES = 0.69–0.93). Peak game intensities were higher in starting players using all sample durations ( p > 0.05; ES = 0.69–1.43) compared with bench players. Shorter sample durations produced higher peak PL·min −1 . Peak intensities were higher during games than training in starting players, indicating training may not adequately prepare players for the most demanding passages of game-play.